DAMPAK REMAJA HAMIL DI LUAR NIKAH TERHADAP ORANG TUA - Basirun, Nurliza Armaya; Nazaruddin, M.; Al Usrah, Cut Rizka; Rizki, Dini (FISIP Universitas Malikussaleh, 2024)
This research is entitled the impact of teenagers getting pregnant out of wedlock on the parents of both parties in the case study of Tanjung Selamat Village, Padang Tualang District. The research method used is a qualitative research method, the data sources used in this research are primary data sources from observations and interviews and secondary data from documentation. This research uses the differential association theory put forward by Edwind H. Sutherland, this theory explains that social deviation in the form of having sex before marriage which results in pregnancy outside of marriage occurs because of interactions between individuals and other individuals, this will have an impact. The findings from this study found that the impact of teenagers getting pregnant out of wedlock on the parents of both parties, such as the social impact in the form of the parents' good name becoming bad, the parents feeling embarrassed, there being disputes and quarrels, and the relationship becoming strained. The psychological impacts include parents being irritable, parents becoming sad, parents getting angry easily, and parents experiencing stress. The economic impact is in the form of economic problems due to the increasing economic burden on parents.